EFFECT OF INQUIRY-BASED LEARNING ON SECONDARY SCHOOL STUDENTS’ ACHIEVEMENT IN GENETICS (UNIZIK Journal of STM Education, 2025)
A fundamental understanding of heredity and variation by secondary school students, predicate the need for teaching methods that foster critical thinking, problem solving and informed decision making which also promote interest and achievement gains in the subject. Thus, informing the current study which sought to examine the effect of inquiry-based learning (IBL) on secondary school students’ achievement in genetics. Despite earlier studies the need to address students’ achievement in genetics persists. Two research questions and two hypotheses guided he study. Quasi experimental pretest-post-test was the study design. Population of the study comprised 13, 596 biology students in Anambra State Public Secondary Schools. The sample size was made up of 300 SS3 biology students (134 male and 166 females) drawn from 6 intact classes of 135 (54 males and 81 females) with experimental group 165 (80 males and 85 females) and control group randomly assigned. The instruments for data collection Genetic Achievement Test (GAT) reliably established at coefficient of 0.86 respectively. Research questions were answered using mean and standard deviation while ANCOVA was used to test the hypotheses at 0.05 level of significance. Results revealed a p-value of 0.000 in achievement. Hence, rejecting the corresponding null hypotheses. Also, with a p-value of 0.905 for male and female students’ achievement, the result accepted the null hypotheses for achievement. By implication, students exposed to IBL achieved significantly higher achievement than those exposed to lecture method. However, there is no significant difference in male and female students’ mean achievement. Major contribution to knowledge of this study is that  this study established that exposure of secondary school students to IBL approaches is essential in enhancing  deeper learning for understanding of genetics and other science subjects, while improving their soft, investigative and critical thinking skills which are necessary in leveraging their future career paths and employability after school.
Keywords: Achievement, Biology, Inquiry Based Learning